Fiscal convergence before entering the EMU - Luca Onorante (European Central Bank (ECB), 2006)
The monetary integration of the acceding countries will proceed in several distinct steps, starting with membership in the European Union (EU), followed by participation in the so-called Exchange Rate Mechanism (ERM) II and ultimately entry into the euro area. This paper addresses the question of whether a reduction of public deficits, such as imposed by the Maastricht fiscal criteria, is a necessary or useful step on the road to the adoption of the euro. The question is addressed by examining the interaction of monetary, fiscal and wage policies and their effects on prices in a monetary union hit by economic shocks. The theoretical model shows that fiscal activism is related with both entry in monetary union and with structural dierences in the national labour markets, and analyses in detail the effect of both factors. As for acceding countries, the conclusion is that the process of deficit reduction should be completed before entry, as suggested by the Maastricht criteria. The chapter also suggests that fiscal constraints on government deficits appear essential in a monetary union when the wage formation is taken into due consideration.
Keywords: E61; E62; H30; 330; European Monetary Union; Fiscal Policy; fiscal rules; monetary policy; Finanzpolitik; Geldpolitik; Eurozone; Lohnpolitik; Wirtschaftliche Konvergenz; Theorie